Organizational Resilience: 30 years of intellectual structure and future perspectives - López-López, Yennia Yahaira Guadalupe; Pérez-Martínez, Norma Guadalupe; García, Víctor Hugo Bañuelos; Martínez, Flor de María García (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. The knowledge structure was analyzed, during the period 1991-2021, on the factors that influenced organizational resilience to distinguish possible synergies, interactions, and new research lines. Design/Methodology/Approach. Using a performance analysis and scientific mapping approach, a bibliometric methodology was used to discover and represent conceptual subdomains and thematic development. This methodology consisted of four phases: (1) detection of research topics, (2) visualization of research topics and the thematic network, (3) discovery of thematic areas, and (4) performance analysis. Results/Discussion. Of the 869 publications on organizational resilience indexed in Scopus, the ones that had the most significant impact on the development of the topic were: Resilience; the concept, a literature review and future directions (2011), Developing a capacity for organizational resilience through strategic human resource management (2011), Developing a tool to measure and compare organizations' resilience (2013), Organizational resilience: Development of a conceptual framework for organizational responses (2011), and Facilitated process for improving organizational resilience (2008). The most important authors were Bhamra, R.; Burnard, K.; Seville, E.; Vargo, J. and Beck, T.E. The driving issues that over time have been closely related to the resilience of organizations were: risk management, standardization and regulation, psychological resilience, ICT resilience, protection and security, health personnel, and reliable organization. Conclusions. In recent years, when the subject has been more developed, it became clear that it is essential to observe risk management, health personnel, reliable organization, and decision-making to manage organizational resilience. Regarding possible future lines of research, the following was found: resilience of security networks, cybersecurity, cyber resilience, disaster management, organizational innovation, sustainable development, and sustainability management.